A Rare Case of Contact Allergy towards Impression Compound Material - Wan Ali, Wan Nor Syariza; Ahmad Tarmidzi, Nor Azura (European Journal of Dentistry, 2021)
Impression compound has been introduced for more than 100 years. Since then, it has been widely used to obtain a preliminary impression of the edentulous arch. Although the use of impression compound has declined markedly over recent years as newer materials have become available, the cost-effectiveness and desirable physical and mechanical properties make this material indispensable in developing countries and teaching institutions. Its high viscosity characterizes impression compound as a mucocompressive impression material, which enables the full depth of the sulcus to be recorded for the retention of complete dentures. Literature reviews revealed that most contact allergies to impression materials are towards polyether, very few are towards alginate and polysulfide, and no reported cases have been found toward impression compound. This case report demonstrates a recent rare case of contact allergy towards impression compound during a routine impression taking for a fully edentulous arch in a 61-year-old woman. The patient developed symptoms of an allergic reaction, and the management of the condition was described.
Keywords: impression compound; allergy; hypersensitivity